Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12866-021-02210-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of GeneXpert MTB/RIF assay versus conventional methods for diagnosis of pulmonary and extra-pulmonary tuberculosis

Abstract: Background Tuberculosis (T.B) is one of the major infectious diseases in the developing countries. The diagnosis of extrapulmonary T.B (EPTB) remains problematic and emergence of resistant strains poses a significant threat. Improved diagnosis of tuberculosis is a global priority for proper control. The study aimed to assess the diagnostic accuracy of GeneXpert MTB/RIF assay for diagnosis of pulmonary TB (PTB) and EPTB and to evaluate the performance of GeneXpert system for demonstrating rifamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 30 publications
2
16
2
Order By: Relevance
“…However, 34 false positive cases were detected by GeneXpert MTB/RIF in this study. It may be because sputum samples of patients display a low MTB burden, which is in line with the research results of Elbrolosy et al[8]. For these reasons, the GeneXpert MTB/RIF and gene chip technology can be combined for joint diagnosis to further enhance the performance in diagnosis of MTB, which is conducive to the evaluation of false positive diagnostic results.…”
supporting
confidence: 66%
“…However, 34 false positive cases were detected by GeneXpert MTB/RIF in this study. It may be because sputum samples of patients display a low MTB burden, which is in line with the research results of Elbrolosy et al[8]. For these reasons, the GeneXpert MTB/RIF and gene chip technology can be combined for joint diagnosis to further enhance the performance in diagnosis of MTB, which is conducive to the evaluation of false positive diagnostic results.…”
supporting
confidence: 66%
“…Furthermore, studies in patients with colonic TB indicate that positive culture can be found in only one-third of patients or even less [ 9 , 10 ]. Although the advanced investigations like polymerase chain reaction and Gene X-pert play a promising role in the diagnosis of pulmonary TB, it has shown poor sensitivity and specificity for the detection of abdominal TB from ascitic fluid samples [ 11 ] compared with sputum [ 12 ] and cerebrospinal fluid [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further shorten the judgment time of results. GeneXpert MTB/RIF (GeneXpert) is a semi-quantitative gene detection technology based on nucleic acid amplification (8). It based on the principle of fluorescence quantitative polymerase chain reaction (PCR): Mtb and its drug resistance can be detected directly from the patient's sputum and other specimens at the same time (9).…”
Section: Introductionmentioning
confidence: 99%